2008
DOI: 10.1159/000151392
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Caspase-8 and Caspase-10 Expression in Rectal Cancer

Abstract: Objectives: To investigate the expression of caspase-8 and -10 in rectal adenoma, adenocarcinoma and the corresponding normal mucosa tissue, and to clarify the relationship between their expression and clinicopathological parameters of rectal cancer. Methods: The expression of caspase-8 and -10 was determined by real-time RT-PCR and immunohistochemistry in 36 rectal adenomas, 93 rectal cancers and 93 corresponding normal rectal mucosa samples. Results: Compared with normal mucosa, the mRNA expression of caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
3
15
1
Order By: Relevance
“…For example, we observed that the pro-apoptotic gene CASP10 was strongly down regulated early after stimulation with LPS, exclusively in humans (Figure S7). Somatic mutations in CASP10 , as well as reduced expression levels of this gene, were found to be associated with a number of different human cancers [41][44]. The observed inter-species differences in the regulation of CASP10 following infection may therefore be related to differences in the rates of cancer across species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we observed that the pro-apoptotic gene CASP10 was strongly down regulated early after stimulation with LPS, exclusively in humans (Figure S7). Somatic mutations in CASP10 , as well as reduced expression levels of this gene, were found to be associated with a number of different human cancers [41][44]. The observed inter-species differences in the regulation of CASP10 following infection may therefore be related to differences in the rates of cancer across species.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of increased expression of caspase-8 in several types of cancer including colorectal and rectal, gastric, pancreatic, and breast cancers [13], [14][17]. Besides, it has been also shown that caspase-8 expression is lost or inactivated in certain types of cancer such as small cell lung cancer, neuroblastoma, gastric carcinoma and hepatocellular carcinoma [18]–[25].…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-8, caspase-10 and caspase-9 are believed to be the initiator caspases at the top of the caspase signalling cascade (46,47). It has been recently reported that caspase-10 expression is downregulated in both rectal adenomas and cancers and may be involved in the pathogenesis of rectal cancer (48). Thus, we surmised that the increased expression of caspase-10 might play a key role in curcumin-induced A549 cell apoptosis.…”
Section: Discussionmentioning
confidence: 85%